Improving History Learning Outcomes Class XE students at SMA Negeri 1 Kaliwungu, Kendal Regency through the Talking Stick Learning Model 2011/2012 Academic Year - Ermiyanto, Dony Dwi (Universitas Negeri Semarang, 2017)
This research is a classroom action research (CAR). Classroom action research (CAR) is a form of reflective investigation that is participatory and collaborative and has a goal to make system improvements, working methods, processes, content, competence, and a situation that begins with planning (planning ), action (action), observation (observation), and reflection (reflecting) until repair or improvement is achieved. The subjects in this study were students of SMA Negeri 1 Kaliwungu XE—still a need for classroom learning outcomes standard of 6.50. Based on the results of this study, it was concluded that learning talking stick models of learning outcomes are 63.625 to 64.50. It can be said to be increased by 0.875. Of the average value of the first and second cycles, 64.50 to 73.625.